Biological mechanism of shockwave in bone. (December 2015) - Cheng, Jai-Hong; Wang, Ching-Jen
Abstract: Shockwave is a rapid, short duration acoustic wave that carries energy and can propagate through tissue medium. This kind of physical force can be a mechanical stimulus that induces biological effects in living tissue. Extracorporeal shockwave therapy (ESWT) acts as a mechanical stimulus which promotes biological healing processes through a mechanotransduction. The biological effects of ESWT are reported such as tissue regeneration, wound healing, angiogenesis, bone remodeling, and anti-inflammation. Until now, however, little is known about the basic mechanism of action of this type of therapy. This article describes the molecular mechanism on the current status of ESWT with pre-clinical and clinical applications for treating disorders in bone. Highlights: ESWT is a novel method in musculoskeletal disorders and other disease. The biologied effects of ESWT may be through mechanotransduction. Applications of ESWT are increasing. ESWT promotes tissue regeneration, wound healing, angiogenesis, bone remodeling, and anti-inflammation.